Catheter ablation of frequent premature ventricular complexes: curative strategy for symptom relief. - Ibarrola-Peña, Juan Carlos; Camacho-Mondragón, Christian Giovanni; García, Rafael; De la Pena-Almaguer, Erasmo; Cortes-Aguirre, Mauricio (Cardiovascular & Metabolic Science)
Introduction: premature ventricular complexes (PVCs) are linked to PVC-induced cardiomyopathy, functional deterioration, and poor quality of life (QOL). Presentation of case: a 54-year-old woman presented for evaluation with dyspnea and palpitations as her primary complaints. She was under follow-up for premature ventricular contractions (PVCs) and had been treated with oral antiarrhythmic therapy (bisoprolol). Despite improvement in chest pain, her response to treatment was poor. She experienced an increase in PVC frequency despite medication up-titration over a three-month follow-up period. She also reported a marked decline in functional capacity, characterized by exertional dyspnea, distress, and palpitations during moderate physical activity. Symptoms persisted at rest, with a significant negative impact on quality of life. As a result, she limited her physical activity to walking due to symptom burden and fear of palpitations. Conclusion: in selected cases, PVCs ablation can effectively relieve symptoms and enhance QOL.